Web-based coffee shop with chatbot integrated - Cheah, Wen Huey (2023)
In a world where coffee stands as an enduring favorite, it has become a daily ritual for many. The global demand for coffee has spurred the growth of tools and an expanding variety of coffee beans. However, in the midst of the evolving coffee culture and the proliferation of trendy cafes, modern coffee websites often lack a truly comprehensive product range. Introducing a web-based coffee shop that caters to coffee enthusiasts' every need. This platform offers an extensive selection of coffee products, a diverse range of beverages, and highquality home brewing tools and equipment. It goes beyond mere merchandise by providing valuable insights into products, brewing techniques, and various coffee-related topics. Recognizing the importance of customer support in the face of such a vast selection, the platform seamlessly integrates a chatbot feature. This intelligent assistant offers not only personalized product recommendations but also around-the-clock support. Customers can find answers to common queries or obtain assistance with orders, day or night, ensuring a seamless and stress-free shopping experience. In summary, this project reimagines the online coffee shopping experience by combining a comprehensive product selection with AI-powered support, ultimately enhancing customer satisfaction.